Impact of vitamin C supplementation on serum ferritin level in hemodialysis patients - Bahman Bashardoust; Anahita Zakeri; Marina Jastan; Firouz Amani; Afshin Habibzadeh; Farnaz Khatami (Society of Diabetic Nephropathy Prevention, 2018)
Background: Iron deficiency anemia is common in patients on maintenance hemodialysis (HD). Serum ferritin is increased in HD patients. Vitamin C supplementation has shown to improve functional iron deficiency and anemia in HD patients. Objectives: In this study we aimed to evaluate the effect of vitamin C supplementation on serum ferritin level. Patients and Methods: In this randomized clinical trial, 39 HD patients were randomly assigned to receive routine therapy with (n=24) or without (n=15) vitamin C 500 mg IV twice a week after each dialysis session for 2 months. Changes in serum ferritin, iron, total iron-binding capacity (TIBC) and transferrin saturation (TS) before and after treatment were measured in each group. Results: Serum ferritin levels before treatment in case and control groups were 1859±1398.5 and 2567.5±1907.8 ng/mL which was significantly decreased to 1084.8±727.9 and 1313.5±1151.5 ng/mL, respectively (P=0.006 and P=0.007). Serum iron, TIBC and TS did not change significantly in each group after treatment. Comparing the mean changes in serum ferritin, iron, TIBC and TS, there was no significant difference between groups. Conclusions: Vitamin C had no effects on serum ferritin, iron and TS.